Effects of irrigation on root growth and development of soybean: A 3-year sandy field experiment - Bui, Khuynh The; Naruse, Toshiya; Yoshida, Hideki; Toda, Yusuke; Omori, Yoshihiro; Tsuda, Mai; Kaga, Akito; Yamasaki, Yuji; Tsujimoto, Hisashi; Ichihashi, Yasunori; Hirai, Masami; Fujiwara, Toru; et al. (Frontiers in Plant Science, 2022)
Increasing the water use efficiency of crops is an important agricultural goal. The root system plays a central role in water uptake. Therefore, this study aimed to understand the response of root development to the water supply. We planted 200 soybean genotypes in sandy soil under irrigated or non-irrigated conditions over 3 years and investigated 14 root traits in addition to plant height and shoot fresh weight to evaluate the response to irrigation. Most of the root traits showed larger values under the irrigated conditions than under the non-irrigated conditions. Three-way ANOVA revealed that the effect of treatments and years were the largest sources of the total variability. The percent variation contributed to the total variability by treatment and year was more than 80%. The tendencies of each trait between irrigated and non-irrigated conditions were similar. However, the actual values fluctuated over the 3 years because the growth of plants in the fields is largely affected by climate, i.e., temperature, sunshine duration, and precipitation). Therefore, the best linear unbiased prediction (BLUP) values for each trait were calculated using the data from 3 years. Principal component analysis (PCA) showed that most traits contributed to PC1, and average diameter, the ratio of thin root length, and the ratio of medium thickness root length contributed to PC2. These results suggested that most root traits were somewhat improved by irrigation. Subsequently, we focused on selecting genotypes that exhibited large improvements in root traits under irrigation compared to non-irrigation using the increment (I-index) and relative increment (RI-index) indices calculated for all traits. Finally, we screened for genotypes with high stability and root growth over the 3 years using the multiple trait selection index (MTSI). Six genotypes, GmJMC130, GmWMC178, GmJMC092, GmJMC068, GmWMC074, and GmJMC081, were selected in the top 10% of genotypes under both irrigation and non-irrigation. The selected genotypes have great potential for breeding cultivars with improved water usage abilities, meeting